HUBUNGAN STRES NEGATIF (DISTRES) DENGAN PERDARAHAN GINGIVA PADA PASIEN RUMAH SAKIT JIWA BANDA ACEH - Sunnati .; Ridha Andayani; C Putroe Ula Rahifa; Sri Rezeki (Journal of Syiah Kuala Dentistry Society, 2019)
Gingival bleeding is an early feature of gingivitis. Gingivitis is characterized by gingival redness,swelling, and bleeding on probing. Gingival bleeding may be caused by local factor and systemicfactors. Negative stress (distress) is thought to be the risk factor of gingival bleeding. Previous studiesshowed that negative stress (distress) may contribute to the severity of gingival bleeding. However, insome cases heavy gingival bleeding was found in the presence of minimal plaque retention. Theobjective of this study was to see the correlation between negative stress (distress) and gingivalbleeding. This study was an analytic cross-sectional study taking Banda Aceh mental hospital. Thesubjects of this study were 58 patients aged between 15 60 years old. There were 30 male and 28female patients. Data was collected from medical record, history taking and clinical examination ofgingival bleeding and oral hygiene index-simplified (OHI-S). Statistic analysis using chi-square testrevealed that there was no correlation between negative stress (distress) to gingival bleeding (p0.05).Conclusion: This study shows that there is no significant correlation between negative stress (distress)to gingival bleeding. Keywords: Gingival bleeding, negative stress (distress), OHI-S